Usage and acceptance of learning management system among students at a public University in Malaysia - Lee, Hwei Ling (2015)
The Learning Management System (LMS) is established to help connect students and lecturers without the confines of the traditional classroom. It is a software environment which is designed to manage user‟s learning interventions as well as deliver learning content and resources to students. However, with every new implementation of a system, there would be both positive and negative feedbacks regarding the system. Research on acceptance of LMS in Universiti Putra Malaysia (UPM) is quite limited. Therefore, this research aims to study the usage and acceptance of Putra LMS among UPM students. The objective of this study is to identify students‟ usage pattern and acceptance of the Putra LMS and the relationship of these factors with perceived usefulness and perceived ease of use of the system. The sampling method used in this research is probability sampling, with the chosen method of stratified sampling as the characteristic of the population being studied is not homogenous. This quantitative research uses self-administered questionnaires that have involved 400 undergraduate and postgraduate students. The findings of the study indicated that the Putra LMS is effective in helping students complete their tasks, is an essential online tool, simple to use, and is accessible at all times. The results of the study is hoped to be able to become a useful guide for academicians, universities, and future researchers alike. The university, UPM, will benefit from the study as they get to know the acceptance of students and lecturers of the LMS system, and work to enhance its features. This research is also hoped to be able to be an additional source of information related to the study of LMS usage in Malaysian universities. This study has given a new insight into the usage and acceptance of LMS among students from various faculties in UPM‟s Serdang campus and it is proven that they have found the system to be easy to use as well as useful in their learning activities.